Penyebab Terjadinya Duplikasi Nomor Rekam Medis di Puskesmas Pandanwangi Kota Malang - Avivah Nur Aini; Gamasiano Alfiansyah; Novita Nuraini; Muhammad Yunus (FORIKES, 2022)
Duplication of medical record numbers has an impact on writing errors in the patient's medical history, especially in the patient's referral letter, so it takes time to correct it, while the patient has to wait a long time. This study aims to analyze the factors that cause duplication of medical record numbers at the Pandanwangi Health Center based on Gibson's performance theory. This type of research was qualitative with interview techniques, observation and documentation. The results of the study were based on individual factors, not all officers knew about the numbering system, the educational qualifications of the officers had not met the standards, the officers had been working for more than two years. Based on organizational factors, facilities and infrastructure had not been used optimally, there was no evaluation from superiors, there was no standard operating procedure for numbering, there was already an organizational structure. Based on psychological factors, rewards or punishments in the form of praise or reprimand, the officer's attitude was less than optimal.Keywords: unit numbering system; duplication; public health center ABSTRAK Duplikasi nomor rekam medis berdampak pada kesalahan penulisan riwayat penyakit pasien terutama pada surat rujukan pasien, sehingga membutuhkan waktu untuk membetulkan, sedangkan pasien harus menunggu lama. Penelitian ini bertujuan untuk menganalisis faktor penyebab terjadinya duplikasi nomor rekam medis di Puskesmas Pandanwangi berdasarkan teori kinerja Gibson. Jenis penelitian ini adalah kualitatif dengan teknik wawancara, observasi dan dokumentasi. Hasil penelitian berdasarkan faktor individu, tidak semua petugas mengetahui tentang sistem penomoran, kualifikasi pendidikan petugas belum memenuhi standar, lama kerja petugas sudah lebih dari dua tahun. Berdasarkan faktor organisasi, sarana dan prasarana belum maksimal penggunaannya, tidak ada evaluasi dari atasan, tidak ada standar prosedur operasional penomoran, sudah terdapat struktur organisasi. Berdasarkan faktor psikologis, penghargaan atau hukuman berupa pujian atau teguran, sikap petugas kurang maksimal.Kata kunci: sistem penomoran unit; duplikasi; puskesmas